Potensi Danau Poso Menuju Geopark Nasional - Lagi, Gina Kurnia Krisliani; Maliangkay, Denny; Selfiardy, Syafrida; Oroh, Hilda Vemmy (Fakultas Ilmu Sosial dan Hukum, 2024)
This research explores the potential of Lake Poso as a national Geopark area with a focus on geological heritage, biodiversity, and unique cultural diversity. The research results show that this area has significant geological evidence of the formation of Sulawesi Island, high biodiversity with endemic species, and a rich cultural heritage of the local community. The potential of Lake Poso as a National Geopark Area can protect and manage existing natural and cultural heritage, encourage sustainable economic development through tourism, and prioritize local wisdom and environmental sustainability. Even though there are obstacles such as limited understanding of the Geopark concept and accessibility, high public awareness and government support can overcome these challenges. The potential of Lake Poso as a National Geopark Area promises protection and preservation of natural and cultural heritage, providing economic and social benefits, as well as educating visitors about Indonesia's natural and cultural riches.